Development of an automatic attitude recognition system: a multimodal analysis of video blogs - Noor Alhusna Madzlan (Tanjong Malim, 2017)
Development of an automatic attitude recognition system: a multimodal analysis of video blogs by Noor Alhusna Madzlan